2019
DOI: 10.1111/ecog.04799
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term demographic surveys reveal a consistent relationship between average occupancy and abundance within local populations of a butterfly metapopulation

Abstract: Species distribution models are the tool of choice for large-scale population monitoring, environmental association studies and predictions of range shifts under future environmental conditions. Available data and familiarity of the tools rather than the underlying population dynamics often dictate the choice of specific methodespecially for the case of presence-absence data. Yet, for predictive purposes, the relationship between occupancy and abundance embodied in the models should reflect the actual populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 79 publications
(127 reference statements)
1
45
0
Order By: Relevance
“…Previous studies have shown that food scarcity and high levels of desiccated host plants at the end of the summer may lead to reduced body mass and even result in starvation of the larvae, which may consequently reduce overwinter survival and cause local extinctions (Kuussaari et al, 2004;Nieminen et al, 2004). Long-term monitoring of the metapopulation has led to a good understanding of the determinants of overall patch quality on the occupancy and abundance, however, little is known about within-patch variation (but see Schulz et al, 2019).…”
Section: Study Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that food scarcity and high levels of desiccated host plants at the end of the summer may lead to reduced body mass and even result in starvation of the larvae, which may consequently reduce overwinter survival and cause local extinctions (Kuussaari et al, 2004;Nieminen et al, 2004). Long-term monitoring of the metapopulation has led to a good understanding of the determinants of overall patch quality on the occupancy and abundance, however, little is known about within-patch variation (but see Schulz et al, 2019).…”
Section: Study Systemmentioning
confidence: 99%
“…This method is increasingly being used in ecological studies as an efficient way to model species occurrences and population dynamics while accounting for spatial and temporal dependencies in the data (e.g. : Myer, Campbell, & Johnston, 2017;Schulz et al, 2019;Ward et al, 2015). In brief, spatial dependency of observations are accounted for using a latent Gaussian random field, which we constructed using a two-dimensional irregular grid (mesh) based on the geographic coordinates of cell centroids.…”
Section: Testing For Oviposition Site Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…Survey data have been used to demonstrate that the long-term persistence and population dynamics (local extinctions and recolonizations) of the metapopulation largely depend on the number of available habitat patches, their area, and their spatial configuration (i.e., connectivity) (Hanski & Ovaskainen 2000;Dallas et al 2019). Other key factors affecting local extinctions and population dynamics are habitat quality (e.g., number of host plants) (Harrison et al 2011;Schulz et al 2019) and genetic characteristics of individuals (Saccheri et al 1998;Niitepõld & Saastamoinen 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other key factors impacting local extinctions and population dynamics are the habitat quality (e.g. amount of host plants; Harrison et al 2011;Schulz et al 2019) and genetic characteristics of the individuals (Saccheri et al 1998;Niitepõld & Saastamoinen 2017).…”
Section: Introductionmentioning
confidence: 99%